Research on formulating a suitable surfactant formulation for the production of liquid detergents for cleaning kitchen utensils in saltwater - Lê Duy Khánh; Tô Lan Anh; Dương Thị Thanh Loan; Nguyễn Thị Nhung; Nguyễn Lê Tú Quỳnh; Nguyễn Khánh Hoàng Việt (Journal of Military Science and Technology, 2022)
Ensuring logistics support is a very important issue for long business trips at sea of Navy. Along with that, factors related to food safety need to receive more attention because of the ubiquity of pathogenic microorganisms in the environment. One of the factors is to ensure the cleanliness of kitchen utensils after use because contaminated kitchen utensils will become a source of microbial contamination of food, resulting in human health effects. However, the lack of freshwater and using not effective detergents in saltwater make it difficult to clean them. The usual detergents have poor cleaning performance in saltwater conditions. Detergents are made by a combination of surfactants and builders, in which the surfactant plays a main important role in product properties. In this study, we have provided six formulations of surfactant mixture with good cleaning performance in saltwater from materials of natural origin. Some of the physicochemical and biological properties were evaluated to select the most suitable formulation for further study into the production of detergents for kitchen utensils. Among the six formulations, formula 4 has a composition including SLES: CAPB: APG in a ratio of 85:5:10 (w/w/w) which exhibited the highest cleaning performance reached of 95,11% against stains from food grease. In addition, this formulation also exhibits good foaming and foam stability (94.37%) as well as good biodegradability comparable to commercial products. The results show the high potential and suitability of formula 4 in the production of liquid detergents for cleaning kitchen utensils in seawater.